Wkład ziemiaństwa w rozwój przemysłu cukrowniczego w województwie kieleckim w latach 1918–1939 - Słabińska, Elżbieta (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2010)
In the interwar period only every sixth estate in the Kielce Province was industrialized. The gentry specialized in agriculture and food-processing industry; however, those fields did not constitute the majority due to the size of plants, their equipment and employment rate. The only exception was sugar industry. Sugar factories “Częstocice”, “Łubna”, “Szreniawa” and “Rytwiany” were established in the 19th century (“Włostów” at the beginning of the 20th century) on the initiative of the gentry who wanted to process raw material produced in their estates. In time, small plants changed into joint stock companies. As in previous years, landlords were not only engaged in the production of the raw material but also became main shareholders of companies as well as members of their management boards, sharing their knowledge and social position. At the same time, they benefited a lot from those activities. Over time, the role they played diminished as their position was gradually taken over by industry and bank capital. Many former shareholders withdrew completely from sugar industry; others kept a small number of shares losing decisive powers in managing companies. Some landlords limited their relation with sugar factories to entering into plantation contracts. However, there is no doubt that they managed to interest local farms in the production of raw materials.